MODELLING THE RELATIONSHIP BETWEEN RETAIL DEVELOPMENT AND ECONOMIC INDICATORS IN EUROPEAN COUNTRIES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. The modern global market requires extraordinary attention to the development of retail trade, which is not only the face of the economy of countries, but also plays a key role in promoting their economic prosperity. In this context, understanding the relationship between retail development indicators and indicators of the state of the economy is necessary given the importance of retail trade as one of the key elements of economic systems and is an important task for scientists and economists. Highlighting the relationship between retail trade and the state of the economy of European countries opens up opportunities for understanding and predicting economic and social trends on the path of Ukraine's accession to the EU, and promotes entrepreneurship. This study aims to model the relationship and establish statistically significant dependencies between the development of retail trade and the economic development of European countries, and to identify indicators that have an impact on the development of the industry. The study established a statistically significant impact of economic growth characteristics on the development of the retail trade industry in European countries in 2005-2022. In particular, it has been determined that the volume of trade turnover depends on such indicators as GDP per capita, consumer inflation and unemployment in the economy. The number of retailers is influenced by the volume of high-tech exports and the Gini index, which measures income inequality in the country. The number of employees in the industry depends on consumer inflation, unemployment and the Gini index. The share of income that is invested in the operating activities of the industry's enterprises depends on the level of consumer inflation, unemployment, the share of research and development expenditures in GDP and GDP per capita. GDP per capita has the strongest positive effect on turnover and consumer inflation on turnover. The unemployment rate has the strongest negative impact on turnover and the number of employees in the industry. The study confirmed the hypothesis about the positive impact of economic development on the retail industry in European countries. An economic system that promotes investment in research and development, aims to reduce unemployment and increase economic efficiency, plays a key role in the development of the retail industry in European countries. Given this, future research should focus on other factors that may influence the development of the retail industry in order to better understand the processes taking place in this area and to develop more accurate and effective strategies to promote its sustainable growth.
Keywords: retail trade, economic development, international relations, market analysis, modelling.